The Role of Interactive Control System In Responding to Strategic Uncertainties of SEOJK PAYDI - Kristina, Andrea Laksmirani; Hermawan, Ancella Anitawati (Jurnal Akuntansi Manado (JAIM), 2024)
SEOJK5/2022 as a novel PAYDI regulation had triggered strategic uncertainty for ABC, where 40% of income was supported by sales of PAYDI. SEOJK5/2022 has several points which change majority of product structures including PAYDI operations. This research discusses how ABC implements interactive control systems (ICS) to face strategic uncertainties, considering there were only few companies had succeeded to respond SEOJK5/2022 well. Qualitative case study method was used in this research, main data collected through interviews and questionnaires. The result concludes that ABC had emphasized the use of ICS in the emergent strategies formulation process, debate and dialogue were carried out intensively at various levels. ABC had succeeded in responding SEOJK5/2022 by making adjustments to all available PAYDI in the company before time limit. During the adjustment period, ABC increased their sales by emphasizing traditional insurance sales. This research contributes additional evidence to levers of control study in facing strategic uncertainties.